2021
DOI: 10.1007/s11199-021-01255-0
|View full text |Cite|
|
Sign up to set email alerts
|

In Their Footsteps or Shadow? Gender Differences in Choosing a STEM Major as a Function of Sibling Configuration and Older Sibling’s Gender and Math Ability

Abstract: Although the association between siblings’ compositional characteristics and educational performance has been extensively studied, the question of whether the features of a sibling group are related to substantive gendered educational preferences has not been examined. Our analysis of the National Longitudinal Survey of Youth 1979 cohort (NLSY-79) Mothers and Children Files (N = 1545; 57% young women; 22% STEM major) showed that siblings’ compositional characteristics matter for STEM major preferences in colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Again, it is hard to explain "why?" since research and facts show inconsistent results on the difference between males and females in mathematics (e.g., Gabay-Egozi et al, 2022;Hyde & Mertz, 2009). Previous study has also found that gender disparities in mathematics are complex, but it is important to note that there are other elements that contribute to gender differences in mathematics (Halpern et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Again, it is hard to explain "why?" since research and facts show inconsistent results on the difference between males and females in mathematics (e.g., Gabay-Egozi et al, 2022;Hyde & Mertz, 2009). Previous study has also found that gender disparities in mathematics are complex, but it is important to note that there are other elements that contribute to gender differences in mathematics (Halpern et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have shown that male students surpass female students in mathematical ability (Gabay-Egozi et al, 2022;Keller et al, 2022), while females are superior to males in terms of communication and language skills (Adani & Cepanec, 2019;Al-Saadi, 2020;Denton & West, 2002). Then what about mathematical communication skills?…”
Section: Discussionmentioning
confidence: 99%
“…She also found that women are often perceived as less competent by their teammates in male-dominated fields like STEM and have less influence on team decision-making processes according to social role theory. Despite their actual knowledge, capabilities, and expertise, this is a result of the fact that women are underrepresented in these settings and atypical (Gabay-Egozi et al, 2022;van der Vleuten et al, 2018). Accordingly, the underrepresentation of women in STEM fields, as well as their atypical roles in engineering and science, may have an impact on how their expertise is assessed (Riegle-Crumb et al, 2016).…”
Section: Stereotype Threat In Stemmentioning
confidence: 99%
“…A recent research on STEM career choices shows that girls who grew up with a predominantly male sibling group and/or with an older sister who was a high achiever in math are more likely to choose a STEM career. Gender educational outcomes are shaped by role model interaction and competitive stimulation of the same gender (Gabay-Egozi et al , 2022).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%